2011
DOI: 10.1111/j.1742-1241.2010.02537.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary incidentalomas: a single-centre experience

Abstract: Majority of PIs are non-functioning adenomas that remain stable in size. Relapse in size and hypopituitarism postoperatively are common. PIs, for which conservative management was initially considered appropriate, did not progress in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
(86 reference statements)
3
21
0
Order By: Relevance
“…Previous studies on incidentally discovered NFPA reported a male preponderance ranging from 52 to 75% (3,8,10). Our data confirm a gender imbalance.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies on incidentally discovered NFPA reported a male preponderance ranging from 52 to 75% (3,8,10). Our data confirm a gender imbalance.…”
Section: Discussionsupporting
confidence: 81%
“…However, more patients are diagnosed because of an imaging study performed for unrelated reasons, the so-called pituitary incidentaloma. The definition of pituitary incidentaloma varies among authors: some include only lesions that satisfy radiographic criteria for pituitary adenoma (3,4), whereas others include all sellar lesion (5,6,7,8,9,10). Pooling the data of 18 902 subjects in a meta-analysis, Molitch (11) reported that the frequency of pituitary adenomas found at autopsy in subjects with no ante-mortem history of pituitary diseases was 10.7% (range, 1.5-31%), but almost all tumors were tiny microadenomas.…”
Section: Introductionmentioning
confidence: 99%
“…1 Based on combined data of micros and macros (weighted heavily towards macros), when hypopituitarism does occur, GH and gonadotrophin deficiency are the most likely to be present, followed by ACTH and TSH deficiency. [3][4][5][6] We have noted that among our patients with micros, those with ACTH-secreting adenomas seem to have a higher prevalence of central hypothyroidism (HT) compared to other micro types (both hormone-secreting and clinically nonfunctioning) of comparable size. We speculated that this might be related to the effects of hypercortisolism on the hypothalamic-pituitary-thyroid axis.…”
Section: Introductionmentioning
confidence: 90%
“…As larger micros may resemble macros in their ability to compromise anterior pituitary function, recent Endocrine Society guidelines recommend testing for hypopituitarism in all patients with an incidentally discovered pituitary adenoma, regardless of size . Based on combined data of micros and macros (weighted heavily towards macros), when hypopituitarism does occur, GH and gonadotrophin deficiency are the most likely to be present, followed by ACTH and TSH deficiency …”
Section: Introductionmentioning
confidence: 99%
“…Also, the majority of the patients had macroadenomas at diagnosis, which is in line with other studies. 19,20 Interestingly, however, the rate of vision loss was much lower in the pituitary incidentalomas cohort compared to CMSMs (2.9 vs 24.1%, P<.01). This could be due to the difference in the actual size of macroadenomas between the two groups.…”
Section: Discussionmentioning
confidence: 87%